Predicting streaming potential in reactive media: the role of pore geometry during dissolution and precipitation - Soldi, Mariangeles (2024)
Dissolution and precipitation processes modify the structure of the porous media at microscale which significantly affects the macroscopic properties of the media. These variations in the pore geometry result in changes in the hydraulic properties that control the groundwater flow, and also modify the electrokinetic properties associated to the displacement of electrical charges carried by the flow which originates the streaming potential. Under the hypothesis of a uniform dissolution or precipitation of the pores and based on the effective excess charge density approach, we present a physically based theoretical model for estimating the effective excess charge density as a function of time. The model is based on the assumption that the pore structure can be represented by an ensemble of capillary tubes with a smooth periodic variation of their radius and a fractal pore size distribution. The analytical expressions obtained to describe the effective excess charge density depend on the chemical parameters of the fluid and the petrophysical properties of the medium. In addition, the periodic variations assumed in the pore geometry represent a more realistic description of a porous medium than considering the pores as constant radii capillaries. These irregularities allow us to include the hysteresis phenomenon in the electrokinetic properties. The expressions of the proposed model have been tested with experimental data consisting of sets of effective excess charge density-effective saturation, permeability-effective saturation, porosity-time and permeability-time values. In all cases, the model is able to satisfactorily reproduce the behaviour of the data.